The regularity of influence of exogenous saccharide on the morphophysiolo gical and biochemical indices of heterotrophic callus culture of fenugreek - Hlushakova, Darya U.; Lohvina, Hanna O.; Yurin, Vladimir M. (Experimental Biology and Biotechnology, 2017)
The article presents results of studying the influence of the type and concentration of the carbohydrate component of the culture medium on the growth rate of fenugreek (Trigonella foenum-graecum L.) callus culture, their cell morphology and total saponins. Eight carbohydrates have been tested at concentrations of 2; 4 and 6 %: monosaccharides glucose and galactose, oligosaccharides sucrose, raffinose, maltose and lactose, polysaccharides inulin and starch. It was shown different reaction of the callus on the saccharides addition. The nature of changes of specific growth rate and total saponins in fenugreek cell culture did not depend on the concentration and type of carbohydrate. The morphology of cells was determined by the growth activity of the callus tissue. High specific growth rate is observed when growing the callus in the presence of 6 % glucose, or 4 % sucrose. Maximum total saponins was found on the nutrient medium supplemented with inulin in all tested concentrations. Among tested variants, the nutrient medium comprising 4 % of sucrose was the most suitable for culturing of fenugreek callus to produce significant amounts of cell biomass with relatively high content of saponins.
Keywords: Trigonella foenum-graecum; fenugreek; callus culture; nutrient medium; monosaccharides; oligosaccharides; polysaccharides; specific growth rate; cell morphology; total saponins